Legal Review of the Recognition of Outsidered Children Based on the Book of Civil Law - Masitah Pohan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Legal review due to the recognition of out-of-wedlock children based on the Civil Code, where it is known that a child is a gift from God Almighty and if the child is born outside the marriage between a boy and a girl without acknowledgment by the parents, the child is not will have a legal relationship with his parents. This research is motivated by the importance of recognizing children born outside of marriage. The purpose of this study was to determine the legal consequences of an out-of-wedlock child if they received recognition from their parents, and to determine the impact on the outside child if they did not receive recognition. The research method used is normative legal research through literature study and using an analytical approach. Based on the results of the research, it is understood that children outside of marriage are children born outside of legal marriages, so with the recognition made by the parents, there will be a civil relationship between the child and the father and mother (Article 280 of the Civil Code).